PENGARUH KOMUNIKASI KELOMPOK NCTZEN INDONESIA TERHADAP PERILAKU MEMILIH NCT DREAM DI ACARA MUSIK MINGGUAN (Survei Pada Followers Akun Twitter nctconfess) - Indah Purnama Sari (2020)
Social media is a social change tool using the internet where social media used by everyone as their communication process that reaches all levels of society to form a group to talk about something that is in common with the group. NCTzen Indonesia is a fan group from the Kpop idol group, NCT Dream that formed from the social media Twitter, nctconfess. The nctconfess followers are considered to be able to influence the activities and behavior of other followers. This research aims to determine the effect of NCTzen Indonesia's communication through twitter on the voting behaviour fellow followers using the S-O-R theory as its foundation. This research uses a quantitative approach with a survey method or questionnaires spreaded through menfess to 100 respondents in the category of followers of Nctconfess and vote NCT Dream during the promotion period. The results based on the correlation test show that there is an average relationship between NCTzen Indonesia's communication with voting behaviour. The result of hypothesis test shows that NCTzen Indonesia's communication affect to Voting Behaviour (Y) which calculated with 1 point obtained t count> t table is 7,671> 1,984 it can be concluded that Ho is rejected and Ha is accepted. Referring to the test results of the coefficient of determination, shows the magnitude of the effect generated by the Communication of NCTzen Indonesia (X) on the Voting Behavior (Y) is 39.81% and the remaining 60.19% is influenced by other factors outside this research. Keywords: NCTzen, NCT Dream, Voting Behavior, Twitter, Kpop